The Effect of Financial Derivative Use on the Probability of Financial Distress: A UK Study - Ashley, James (2015)
An analysis of 50 FTSE 100 companies and the relationship between derivative use and the probability of financial distress, as measured by the ALtman Z-Score. I find that derivativeshave an insignificant affect upon the probability of financial distress